2008
DOI: 10.1016/j.jpcs.2008.06.106
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pressure effects on the spin state of ferric ions in the [Fe(sal2-trien)][Ni(dmit)2] spin crossover complex

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d m a n u s c r i p t Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…Regarding this issue, very few attempts have been noticed to record the (p-T) phase diagram by using various detection techniques such as optical reflectivity [19][20][21][29][30][31], magnetic techniques [15][16][17][18][32][33][34], X-ray and neutron diffraction [35][36][37][38][39]. This lack of data could be explained by the difficulty to obtain small variations in the applied pressure in both loading and unloading processes, at variable temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this issue, very few attempts have been noticed to record the (p-T) phase diagram by using various detection techniques such as optical reflectivity [19][20][21][29][30][31], magnetic techniques [15][16][17][18][32][33][34], X-ray and neutron diffraction [35][36][37][38][39]. This lack of data could be explained by the difficulty to obtain small variations in the applied pressure in both loading and unloading processes, at variable temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…, where the application of 50 MPa induced a very large increase of the hysteresis width together with signs for an irreversible feature of these modifications [17]. Even though never clearly evidenced; other signs of irreversible effects of pressure were suspected in previous studies of SCO materials [10,19,48].…”
Section: Ex Situ Pressure Effectsmentioning
confidence: 87%
“…From the experimental point of view, many counter-examples have been reported so far [15]. For example, non-expected hysteresis broadening [16] as well as irreversible behaviors were reported for some compounds [10,17]. Even in a family of very similar complexes, a variety of high pressure behaviors can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…37 Elsewhere, since the reference case of [Fe(phen) 2 (NCS) 2 ], 6 expectation (v) has been confirmed in numerous investigations ( Fig. 20.1) 19,24,[38][39][40][41] but nonlinear behaviour has been reported as well in complexes that nonetheless clearly fulfil expectations (i)-(iii). 16,37 In the same manner, while the reversibility of pressure effects, expectation (vii), is often reported, 42, 43 some nonreversible effects have also been observed.…”
Section: Pressure-induced Sco: Expectation Versus Observationmentioning
confidence: 75%
“…16,37 In the same manner, while the reversibility of pressure effects, expectation (vii), is often reported, 42, 43 some nonreversible effects have also been observed. 24,28 All attempts to rationalize the behaviour of SCO materials under pressure using comparative analysis of data finally came to the conclusion that the large diversity of situations is almost unpredictable. For instance, analysis of X-ray absorption spectra of eight iron mononuclear or polymeric complexes showed that about half of the investigated materials fulfilled the above expectations, but the other half showed clear differences, notably on (v).…”
Section: Pressure-induced Sco: Expectation Versus Observationmentioning
confidence: 99%